Employing artificial intelligence techniques to make films (Al-Academy, 2024)
The film business is one of the many industries that artificial intelligence is inexorably involved in due to the rapid advancement of technology. Artificial intelligence benefits the industry at every stage of the production cycle. This paper focuses on five phases: script writing in AI, picture generation in AI, voice recordings in AI, make animation in AI, movie editing, with a presentation of artificial intelligence tools.This research highlights that artificial intelligence (AI) technology and human artistic production are essential for the robust growth of the film business only when they complement one another by examining the advantages and possible hazards. The research encourages the new trend towards employing artificial intelligence to produce short films for graduate and undergraduate students, researchers, and those interested, and to benefit from the free features available on artificial intelligence websites that do not require expensive purchases to obtain benefits